1998
DOI: 10.1076/ceyr.17.2.183.5597
|View full text |Cite
|
Sign up to set email alerts
|

Tear changes in contact lens wearers following overnight eye closure

Abstract: Uncomplicated daily use of soft CLs does not appear to alter certain tear proteins compared with baseline levels. Uptake of these proteins by the CL does not appear to deplete the tear protein levels. Overnight levels of all tear proteins were increased, compared to daily CL wear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…These characteristics, including the levels of tear proteins following overnight eye closure, with and without contact lens wear, have been investigated previously. [26][27][28] In these studies microcapillary tubes were used for tear collection immediately after opening the eye and changes in the levels of tear proteins were Copyright 2014 The Association for Research in Vision and Ophthalmology, Inc. www.iovs.org j ISSN: 1552-5783 measured. Microcapillary tear collection is a suitable method for aqueous tear collection; however, it is not ideal for tear lipid collection.…”
mentioning
confidence: 99%
“…These characteristics, including the levels of tear proteins following overnight eye closure, with and without contact lens wear, have been investigated previously. [26][27][28] In these studies microcapillary tubes were used for tear collection immediately after opening the eye and changes in the levels of tear proteins were Copyright 2014 The Association for Research in Vision and Ophthalmology, Inc. www.iovs.org j ISSN: 1552-5783 measured. Microcapillary tear collection is a suitable method for aqueous tear collection; however, it is not ideal for tear lipid collection.…”
mentioning
confidence: 99%
“…Major tear proteins consist of lysozyme (Fullard 1988), lactoferrin (Flanagan and Willcox 2009), albumin (Carney et al 1997), lipocalin (Glasgow et al 1995), IgA (Stapleton et al 1998) and phospholipase (Nevalainen et al 1994). Frequently detected tear proteins in contact lens extracts include lysozyme, lactoferrin, lipocalin, proline rich protein-4 and keratins (Zhao et al 2008;Emch and Nichols 2009).…”
Section: Introductionmentioning
confidence: 99%
“…According to some studies, the daily use of CLs has no effect on the amount of cells [10], total protein content [6,10,26], the content of sIgA [14], lysozyme [5,14], albumin [5,14] or lactoferrin [5] in tears. Furthermore, some studies have reported the tear sIgA content to increase due to the daily use of CLs [13,24,27] and another to decrease [12].…”
Section: Introductionmentioning
confidence: 99%
“…IgA isotypespecific antibodies reactive with Escherichia coli and Staphylococcus epidermidis have been reported to be present at lower levels in CL wearers than in normal subjects. In addition, the composition of tear proteins during the overnight use of CLs has been reported to change: both the total protein content and the C3, C4 and sIgA content of tears decreased after the overnight use of CLs [26].…”
Section: Introductionmentioning
confidence: 99%